1997
DOI: 10.1016/s0022-5347(01)64140-5
|View full text |Cite
|
Sign up to set email alerts
|

Transurethral Needle Ablation of the Prostate: A Urodynamic Based Study With 2-Year Followup

Abstract: Transurethral prostate resection is a safe and effective technique for treating lower urinary tract symptoms related to benign prostatic hyperplasia. The technique can be performed in the office as an outpatient, or as a same day surgical procedure, using topical anesthesia with intravenous sedation, if necessary. In the majority of patients subjective and objective improvements were sustained for the duration of this study, which included 2-year followup with pressure-flow studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 23 publications
1
39
0
2
Order By: Relevance
“…The long–time efficacy of transrectal HIFU has to be compared to competing thermoablation techniques, such as low– and high–energy transurethral microwave thermotherapy (TUMT), transurethral needle ablation (TUNA) and interstitial laser coagulation [1, 2, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15]. It needs to be emphasised that there are only few long–term data available with follow–ups comparable to our series.…”
Section: Discussionmentioning
confidence: 99%
“…The long–time efficacy of transrectal HIFU has to be compared to competing thermoablation techniques, such as low– and high–energy transurethral microwave thermotherapy (TUMT), transurethral needle ablation (TUNA) and interstitial laser coagulation [1, 2, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15]. It needs to be emphasised that there are only few long–term data available with follow–ups comparable to our series.…”
Section: Discussionmentioning
confidence: 99%
“…However, only low– and high–energy transurethral microwave thermotherapy (TUMT) can reliably be performed under topical anesthesia only [15, 16, 17]. TUNA and interstitial laser coagulation require topical anesthesia supplemented with intravenous sedoanalgesics in a substantial number of patients [9, 10, 14, 18, 19]. TUVP, Holmium laser resection, VLAP and transrectal HIFU require regional or general anesthesia as TURP [20, 21, 22, 23, 24, 25].…”
Section: Discussionmentioning
confidence: 99%
“…For high–energy TUMT, the respective percentages range from 4 to 15% within 12 months after therapy. Following TUNA, Rosario et al [11]reported that 31% had to undergo prostatectomy within 12 months after therapy, in the series of Steele and Sleep [10]this percentage was 12.7%. Schulman and Zlotta [27]presented 3–year follow–up data of 49 patients after TUNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most series found no retrograde ejaculation and no impotence at all after this procedure [26, 31, 32, 33, 34, 35]. Only the prospective multicenter US trial found less than 1 and 2% of retrograde ejaculation and impotence respectively [36].…”
Section: Alternative Instrumental Techniques For Bph: Laser Therapy mentioning
confidence: 99%